Preparation and optical properties of worm-like gold nanorods - Huang, Haowen; He, Chaocai; Zeng, Yunlong; Xia, Xiaodong; Yu, Xianyong; Yi, Pinggui; Chen, Zhong (Journal of colloid and interface science, 2008)
A type of worm-like nanorods was successfully synthesized through conventional gold nanorods reacting with Na 2S 2O 3 or Na 2S. The generated worm-like gold nanorods comprise shrunk nanorod cores and enwrapped shells. Therefore, a gold–gold sulfide core–shell structure is formed in the process, distinguishing from their original counterparts. The formation of the gold chalcogenide layers was confirmed by transmission electron microscopy and X-ray photoelectron spectroscopy. Experimental results showed that the thickness of the gold chalcogenide layers is controllable. Since the increase of shell thickness and decrease of gold nanorod core take place simultaneously, it allows one to tune the plasmon resonance of nanorods. Proper adjustment of reaction time, temperature, additives and other experimental conditions will produce worm-like gold nanorods demonstrating desired longitudinal plasmon wavelength (LPW) with narrow size distributions, only limited by properties of starting original gold nanorods. The approach presented herein is capable of selectively changing LPW of the gold nanorods. Additionally, the formed worm-like nanorods possess higher sensitive property in localized surface plasmon resonance than the original nanorods. Their special properties were characterized by spectroscopic methods such as Vis–NIR, fluorescence and resonance light scattering. These features imply that the gold nanorods have potential applications in biomolecular recognition study and biosensor fabrications. Worm-like gold nanorods (b) can be produced from the as-synthesized nanorods (a) reacting with Na 2S 2O 3. An approach capable of continuously increasing longitudinal plasmon wavelength of new gold nanorods is developed.